Beyond boundaries? Disability, DIY and punk pedagogies. Issue 1 (May 2023) - Stewart, Francis; Way, Laura
DIY is often viewed as a core element of punk, an aspect that enabled activism against an assumed authority and power (Guerra, 2018; Martin-Iverson, 2017). It is therefore often lauded as a means of engaging with/utilising punk in a pedagogical sense (Bestley, 2017; Cordova, 2016). It should be capable of working in tandem with education in developing and encouraging the 'movement against and beyond boundaries' (hooks, 1994). However, this is not necessarily simple or straightforward to realise through one's own pedagogical practices, especially when one considers them through an intersectional lens. We argue that punk scholarship on DIY fails to account for its capacity to support ableist ideologies and structures - incorporating it into punk pedagogy in an uncritical manner risks further deepening asymmetrical power relations in regards to disability and the adversity that people with disability experience. We utilise collaborative auto-ethnography to unpack some of the complexities involved in pursuing punk pedagogical practices and unpacking the aforementioned critique of DIY further. We consider how DIY can/could potentially be a powerful, empowering pedagogical tool and consider the ways DIY purports a damaging, ableist narrative, which at times can even aid the neoliberal agenda within higher education. The necessity for punk pedagogies to be underpinned by considerations of intersectional issues, both from the viewpoint of the teacher and the students, is demonstrated through our use of critical disability theory as an analytical tool.